2021
DOI: 10.3389/fenrg.2020.610577
|View full text |Cite
|
Sign up to set email alerts
|

Nexus Between Carbon Emissions, Energy Consumption, Urbanization and Economic Growth in Asia: Evidence From Common Correlated Effects Mean Group Estimator (CCEMG)

Abstract: This study investigates the dynamic relationships between carbon emission, urbanization, energy consumption, and economic growth in a panel of 42 Asian countries for the period 2000–2014 using dynamic common correlated effects panel data modeling. This study employs second generation cross-sectional Pesaran (J. Appl. Econom., 2007, 22(2), 265-312) panel unit root, Westerlund panel cointegration tests (Econom. Stat., 2007, 69(6), 709-748), and Pesaran’s (Econometrica, 2006, 74(4), 967-1012) common correlated ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…On the basis of these fascinating findings, the authors conclude that the selected African countries are linked through economic growth, FDI inflows, technological advancement, tourism development, and governance. Furthermore, CADF and CIPS unit root testing were adopted because of their effectiveness in stationary checking, as posited in a series of investigations [111,112,130]. Table 4 demonstrates the CADF and CIPS, revealing that it is not feasible to disprove the null hypothesis; however, none of the series (lnCO 2 , lnECG, lnFDI, lnTOUR, and lnGOV) were found to be stationed at the first difference level.…”
Section: Cross-sectional Dependency Testmentioning
confidence: 99%
“…On the basis of these fascinating findings, the authors conclude that the selected African countries are linked through economic growth, FDI inflows, technological advancement, tourism development, and governance. Furthermore, CADF and CIPS unit root testing were adopted because of their effectiveness in stationary checking, as posited in a series of investigations [111,112,130]. Table 4 demonstrates the CADF and CIPS, revealing that it is not feasible to disprove the null hypothesis; however, none of the series (lnCO 2 , lnECG, lnFDI, lnTOUR, and lnGOV) were found to be stationed at the first difference level.…”
Section: Cross-sectional Dependency Testmentioning
confidence: 99%
“…For this, due to cross-sectional dependence, the Pesaran unit root test (CIPS test) was used ( 22 ). If the panel data are cross-sectionally dependent, using panel data unit root tests such as Im, Pesaran, and Shin (IPS), Levin, Lin, and Chu (LLC), and Augmented Dickey Fuller - Fisher (ADF-Fisher) will produce misleading results and raise the risk of erroneous unit root results ( 23 ). By converting the IPS test and considering the cross-sectional dependence, Pesaran has proposed a test to check the presence or absence of a unit root, which is known as the CIPS test ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the Westerlund cointegration test can be used for both cross-sectional dependence and cross-sectional independence ( 20 ). If the cross-sectional dependence is proved, the Westerlund bootstrap method should be used ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that urbanization has affected carbon emissions in multifaceted and complex ways [ 10 ]; such effects could be positive [ 11 ], negative [ 12 ], offering no significant effect [ 13 ], or described as a “hump-shaped” relationship [ 14 ]. Urbanization refers to a series of changes, such as population shift, land use change, lifestyle change and industrial restructuring, all of which might affect carbon emissions in different ways [ 14 , 15 , 16 , 17 ]. Furthermore, some research has focused on the impact threshold of urbanization on carbon emissions to find the optimal level of urbanization for sustainable development [ 18 ].…”
Section: Introductionmentioning
confidence: 99%